Pyroelectric properties of ferroelectric 0-3 composites near matrix transition temperature - Chew, Khian Hooi; Choy, C.L.; Shin, F.G.; Ploss, B.; Chan, H.L.W. (2005)
The pyroelectric properties of a ferroelectric 0-3 composite in the vicinity of the matrix Curie temperature is examined theoretically by incorporating the effects of interfacial charge. A dip predicted in the pyroelectric coefficient as a function of temperature of the composite is associated with the contribution of the secondary pyroelectric effect and/or with incomplete charge compensation of the polarization heterogeneity. At the Curie point of the matrix, the magnitude of the secondary pyroelectric coefficient may be relatively large and cannot be neglected.